Bog bodies Face to face with the past - Giles, Melanie (Manchester University Press, 2020)
The 'bog bodies' of north-western Europe have captured the imagination of poets as much as archaeologists, confronting us with human remains where time has stopped - allowing us to come 'face to face' with individuals from the past. Their exceptional preservation allows us to examine unprecedented details of both their lives and deaths, making us reflect poignantly upon our own mortality. Yet this book argues that they must be resituated within a turbulent world of endemic violence and change, reinterpreting the latest Continental research and new discoveries in this light. The book features a ground-breaking 'cold case' forensic study of Worsley Man: Manchester Museum's 'bog head' and brings the bogs to life through both natural history and folklore, as places that were rich, fertile, yet dangerous. Finally, it argues that these remains do not just pose practical conservation problems but philosophical dilemmas, compounded by the critical debate on if - and how - they should be displayed, with museum exemplars drawn from across the globe